A combination of three muramyl peptides derived from gramnegative bacteria in immunotherapy of chronic pyodermia - O. V. Kalyuzhin (SPb RAACI, 2020)
The aim of the present study was to evaluate the clinical efficacy of a standardized combination of three muramyl peptides containing a residue of meso-diaminopimelic acid (Polymuramyl), as well as effects of this immunomodulator on the lymphocyte subpopulation profile, function of circulating neutrophils, and concentrations of serum immunoglobulins in the patients with chronic recurrent pyoderma. Thirty-five men (34.5±10 years) with exacerbation of chronic pyoderma (osteofolliculitis, folliculitis, sycosis, furunculosis) were randomized into two groups matched by age and clinical manifestations of the disease. In the comparison group (n = 17), the patients received standard treatment. In the main group (n = 18), in addition to the same standard treatment, the patients received intramuscular injections of Polymuramyl at a dose of 200 mg daily from day 1 to 5 of the study. The overall assessment of the treatment efficacy was performed on the day 14, and at 1 and 6 months of observations. Induction and maintenance of complete clinical remission were assessed as “significant improvement”; induction and maintenance of partial remission were considered to be “improvement”; persistent signs of skin inflammation and lack of remission were assessed as “lack of effect”. Immunological parameters were studied on days 0 and 14, and then at 1 and 6 months of the study. Addition of Polymuramyl to the standard treatment caused a marked tendency towards increased proportion of the patients with «significant improvement» or «improvement» on the day 14: total ratio of the patients with any clinical improvement was 24% higher, and the relative number of the patients with "lack of effect" was five-fold lower than in the comparison group (p=0.076). A trend towards improved clinical efficacy, according to the above criteria, was maintained after 1 and 6 months of the study. At 6 months of the follow-up, the proportion of patients without pustules/furuncles in the main group (9 out of 18) exceeded that in the comparison group (3/17, p = 0.047). Significant inter-group differences and dynamics of indicators of neutrophil functions, subpopulation composition of lymphocytes and concentrations of immunoglobulins in serum were not detected. However, in the main group after the 6-month observation, there was an upward trend in the absolute number of T-cells due to CD3+CD4+ subpopulation, as well as serum IgA concentration. The results of this study are in accordance with previously published data, thus indicating the ability of Polymuramyl to accelerate regression of clinical manifestations of chronic pyoderma and induce sustained remission of this disease. At the same time, the design of present investigation and the timing of taking biological samples for laboratory tests did not allow to register significant changes in most of the studied systemic immunological parameters under the influence of immunomodulator, except for the previously described modulation at the level of pro- and anti-inflammatory cytokines.